(untitled) (Docentes 2.0 Journal, 2024)
Learning Object (LO), which enhances teaching strategies and student autonomy. The objective of this research was to analyze the influence of the design and implementation of the LO on the topic of linear equations of the Logical Reasoning course on the academic performance of the Autonomous University of Carmen students. The research was based on constructivist theory, hypothetical deductive method, positivist paradigm with quantitative approach, quasi-experimental design, and cross-sectional correlational method, with two experimental groups and one control group with pretest-posttest. A non-probabilistic sample was obtained for the convenience of 62 students distributed in the participating groups. Two objective tests of three dimensions and seven indicators were used to evaluate the student’s abilities in linear equation instruments to measure academic performance. We were validated with reliability of 0.86 and 0.85 in the pretest-posttest. ANOVA test was applied to check the homogeneity between the groups before the experiment, and no significant statistical differences were observed. The results showed significant statistical differences in academic performance between the experimental and control groups, favoring the groups that used OA. Furthermore, the skills students developed the most when interacting with the LO were using linear equations to solve algebraic problems.